Indigenas y sacerdotes - Centro de Estudios Teológicos de la Amazonía (CETA) (My University, 1900)
SPANISH: Se observó a un grupo de indigenas Aguarunas varones en compañia de los sacerdotes.
ENGLISH: A group of indigenous men Aguarunas was observed in the company of priests.

SPANISH: Se observó a un grupo de indigenas Aguarunas varones en compañia de los sacerdotes.
ENGLISH: A group of indigenous men Aguarunas was observed in the company of priests.
Indigenous people and priests
Keywords: Iquitos (Perú)|~|Native Communities|~|Perú|~|Indigenous or Native populations|~|Religion|~|Evangelization|~|Iquitos (Perú)|~|Comunidades Nativas|~|Perú|~|Poblaciones Indigenas u Originarias|~|Religion|~|Evangelización|~|Iquitos (Peru)|~|Native Communities|~|Peru|~|Indigenous or Native Populations|~|Religion|~|Evangelization